Foraging Behaviour of Damage-causing Birds in Table Grape Vineyards in the Orange River Valley, South Africa - Herrmann, E.; Anderson, M.D. (South African Journal of Enology and Viticulture, 2016)
The foraging behaviour of damage-causing birds in table grape vineyards was examined in the Orange River valley, Northern Cape Province, South Africa during the summer harvest season from November 2001 to January 2002. Based on a sample of 300 foraging acts observed, it was found that mixed-feeder species fed more on grapes during the first month of the harvest (November), when only about 13% of the vineyards bore ripe grapes, than during the subsequent two months (December and January). During the latter two months, insects were a more preferred food item, while grape foraging declined significantly despite the increased availability of grapes, suggesting a shift in their dietary preferences during the course of the harvesting season. A daily bimodal feeding pattern was also detected, with birds feeding more regularly on grapes and other food items from early to late morning and in the late afternoon, with a marked decrease during midday. There was also a preference for feeding from the top rather than from the side or bottom of bunches. There were clear differences in foraging strategies among the most commonly recorded species when these were not feeding on grapes. Mixed feeders fed on invertebrates by gleaning vine bark and foliage, hawking, or foraging in ground litter. Granivorous species generally foraged for plant matter, such as seeds, on the ground, but also foraged on grapes during the early stages of the harvest season (November).